Japanese Zen Schools and the Transition to Meiji: A Plurality of Responses in the Nineteenth Century - Mohr, Michel (Japanese journal of religious studies, 1998)
This article scrutinizes the lives of specific figures affiliated with the three main Zen traditions; it presents firsthand information on their activities from the end of the Tokugawa period through the first decades of the Meiji era. Changes in the political structure and the ensuing economic or social transformations surprisingly did not fundamentally alter the way these Buddhists apprehended their respective legacies. Official pressure encouraged them to put more emphasis on the education of commoners and they shared the global trend to give more importance to lay supporters. The content of their teachings, however, primarily appears to reflect what this paper calls "the shrouded continuity" between the Tokugawa and Meiji eras. The teachers and laypersons examined here also illustrate the diversity that pervaded Meiji Buddhism despite the new government's efforts to centralize all Buddhist institutions; they further bear testimony to the fact that the mutual influence among representatives of different traditions often went beyond artificial sectarian boundaries.